Assessing Efficiency in State Universities: Evidence from the Analytical Hierarchy Process - Panjaitan, Rido Parulian; Sugiri, Dani; Waluyo, Budi (Universitas Negeri Surabaya, 2025)
The introduction of agencification in state universities, marked by the provision of varying degrees of autonomy, aims to improve service quality and operational efficiency. This study investigates the efficiency of state universities through the lens of agencification, i.e., the use of semi-autonomous or autonomous agencies to deliver public services. The Analytical Hierarchy Process is employed to identify and prioritize key criteria influencing university performance. Drawing on semi-structured interviews and focus group discussions with university managers, policymakers, and academics, we reveal twelve critical factors that contribute to efficiency. The findings reveal an urgent need for innovation across leadership, human resource management, information technology, strategic planning, and governance. The findings highlight the role of visionary leadership, effective human resource management, and stringent internal controls as the dominant criteria. We explore the challenges faced by state universities, including the complexities of autonomy models and bureaucratic constraints. The results imply that while university autonomy can enhance operational efficiency, it must be balanced with accountability mechanisms to prevent disparities. This research contributes to the efficiency scholarship by explaining actionable insights for policymakers and university managers to improve service quality in contemporary governance frameworks.